2017
DOI: 10.4172/2472-1654.100043
|View full text |Cite
|
Sign up to set email alerts
|

Job Preferences of Doctors for Working in Rural Islamabad Capital Territory, Pakistan: a Discrete Choice Experiment

Abstract: Background: Developing countries are facing acute shortage of human resource in rural/remote areas. Effective management and retention of human resource for health are related to efficient financing and lucrative incentives packages. This study focused on preferred incentives of doctors for working in rural and resource constrained areas of Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 14 publications
4
25
0
Order By: Relevance
“…Pakistan is one of 57 countries with a serious deficiency in the health workforce. 353 Pakistan has a doctor-to-patient ratio of 1:1300, doctor-to-nurse ratio of 1:2·7, and nurse-topatient ratio of 1:20. 354 There are many informal healthcare providers in Pakistan, comprised of unqualified allopathic providers (eg, rural doctors or drug shop retailers), traditional healers, faith healers, Unani healers, and semi-qualified allopathic providers (eg, medical assistants, technicians, and community health workers).…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…Pakistan is one of 57 countries with a serious deficiency in the health workforce. 353 Pakistan has a doctor-to-patient ratio of 1:1300, doctor-to-nurse ratio of 1:2·7, and nurse-topatient ratio of 1:20. 354 There are many informal healthcare providers in Pakistan, comprised of unqualified allopathic providers (eg, rural doctors or drug shop retailers), traditional healers, faith healers, Unani healers, and semi-qualified allopathic providers (eg, medical assistants, technicians, and community health workers).…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…Being enrolled in a special track, in which the scholarship tied to compulsory service provided for those recruited from rural areas, in addition to being recruited from rural areas and received a rurally enhanced curriculum, was associated with better rural preference [48,49] [50,53], spouse employment [53], access to electricity and water supply [36], transportation [49], were among the key reasons for unwillingness to work rurally There is evidence that preference to work in rural locations is associated with: short travel time to work [91], availability of transportation for official and unofficial use [76], positive perception of living conditions [47], and good educational facilities and connectivity [56]. However, in other studies, associations were not found between rural preference and: housing allowance or support [58,75], access to a vehicle [58] and spouse and child education [34] Overall better living conditions [6,10,11,35,45,65,70,71], housings [76,92], basic infrastructure (i.e., electricity, water, communications connectivity) [52,57,59,88], transportation [57,72,74,76], access to nearest town [41], and children schooling facilities [73], were also important attributes to rural preference. Females regarded housing provision higher than males [58,74] [53,…”
Section: Preference Bmentioning
confidence: 99%
“…Pakistan rank sixth in the world population wise and as per its requirement the health human workforce in quite insufficient. Pakistan is one of the 57 countries that critically deficient in human health resource [42]. In Pakistan doctor to patient ration is 1:1300, nurse to patient ratio is 1:20 whereas, doctor to nurse ratio is 1:2.7.…”
Section: Health System Human Resource Situationmentioning
confidence: 99%